2020
DOI: 10.1007/s00181-020-01890-8
|View full text |Cite
|
Sign up to set email alerts
|

Taxation, credit frictions and the cyclical behavior of the labor wedge

Abstract: Labor-income and consumption taxes are often referred to as the primary causes of the labor wedge and differences in hours worked across countries. While this can be potentially true in the long-run, its premise for explaining the cyclical behavior of the labor wedge is questionable. Using U.S. data over 1955-2019, this paper first studies whether taxation explains the cyclical behavior of the labor wedge. It is shown that the tax wedge, which combines both types of taxes, fails in accounting for the countercy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The authors concluded that both the tax structure and mainly the economic growth strongly affect the tax and administrative burden laid on enterprises in India. Enterprises showing economic growth and subject to changing tax burden find tax burden less difficult to handle [7,8,9]. The question of whether an enterprise´s ability to pay tax is affected by the amount of corporate income was addressed by a hypothesis claiming that tax burden is more demanding with a higher income.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that both the tax structure and mainly the economic growth strongly affect the tax and administrative burden laid on enterprises in India. Enterprises showing economic growth and subject to changing tax burden find tax burden less difficult to handle [7,8,9]. The question of whether an enterprise´s ability to pay tax is affected by the amount of corporate income was addressed by a hypothesis claiming that tax burden is more demanding with a higher income.…”
Section: Introductionmentioning
confidence: 99%